Descendants of Migrants in the Italian Context: The “Social Construction of Illusion” - Girardi, Davide (Italian Sociological Review, 2025)
For the past two decades, young people with a migration background or born in Italy to immigrant parents have progressively become an increasingly important component in numerical terms, especially in a country marked by a demographic crisis that is now well established. Nevertheless, this numerical prominence has not yet been translated into adequate social recognition. On the contrary, the repeated stalling of proposals to reform the institution of citizenship suggests that it is possible to use Sayad’s category of “illusion” to speak of the “social construction of illusion”. This paper analyses the characteristics of this process, which sees the children of immigrants who grew up or were born in Italy particularly affected in the following dimensions: a flattening of linguistic requirements within schooling, without the opening to a broader socio-cultural recognition; a reduced social mobility compared with their parents, reinforced by the phenomena of educational channelling; a symbolic invisibility continually reproduced by the lack of reform (by birth) of the institution of citizenship. In this framework, the “voice” dynamics implemented by young descendants of migrants (especially through associations) constitute an important attempt to deconstruct this process. However, there is a need for inclusive policies with a strong symbolic connotation, capable not only of increasing the actual chances of social mobility of young descendants of migrants, but also of getting them out of the illusion of a “quasi-citizenship”. Only in this way will it be possible to prevent the “frustration of second generations”.